Visual and physiological outcomes of scleral lens wear. Issue 1 (February 2019) - Schornack, Muriel; Nau, Cherie; Nau, Amy; Harthan, Jennifer; Fogt, Jennifer; Shorter, Ellen
Highlights: Scleral lenses improve visual acuity in patients with corneal irregularity, ocular surface disease, and refractive error. Scleral lenses reduce the severity of corneal staining in patients with ocular surface disease and corneal irregularity. Patients who wear scleral lenses may be able to reduce their use of topical ophthalmic medications and lubricants. Adverse ocular findings are reasonably common in scleral lens wearers, but sight-threatening complications rarely occur. Abstract: Purpose: To describe patient-specific outcomes of scleral lens wear utilizing a variety of lens designs across multiple practice settings as reported in an international practitioner survey. Methods: An electronic survey was administered to eye care providers who prescribe scleral lenses in which they were asked to describe their most recently examined established scleral lens patient. Data was collected on patient characteristics, lens designs, wearing schedules, care products, and visual and physiological outcomes of lens wear. Descriptive analysis of data was performed. Results: A total of 292 responses were received. Participants represented 26 countries. The most commonly reported indication for scleral lens wear was corneal irregularity (87%) followed by ocular surface disease (8%), refractive error (4%) and 1% with multiple indications. Visual acuity improved from 0.4 ± 0.4 (mean ± SD) to 0.1 ± 0.2 in eyes with corneal irregularity (p < 0.001), from 0.3 ± 0.3 to 0.1 ± 0.3 in eyes with ocular surface disease (p < 0.001), and from 0.1 ± 0.1 to 0.0± [0.1] in eye with refractive error (p = 0.01). Prior to scleral lens wear, corneal staining was present in 55% of patients; staining was present in only 35% of patients following scleral lens wear. The number of topical ophthalmic drops needed decreased from 1.7 ± 0.9 to 0.8 ± 0.8 in patients with corneal irregularity (p < 0.001) and from 3.5 ± 1.7 to 1.1 ± 1.0 in patients with ocular surface disease (p < 0.001). The number of drops used by patients with refractive error remained stable, with these patients using an average of 2.0 ± 1.0 drops prior to scleral lens wear and 1.7 ± 1.5 drops following scleral lens wear. Conclusions: Patients with corneal irregularity experienced the greatest improvement in visual acuity, but patients with ocular surface disease and refractive error also achieved better visual acuity with scleral lenses. Ocular surface condition improved in patients with both corneal irregularity and ocular surface disease; patients with ocular surface disease experienced the most dramatic improvement. Patients who wore scleral lenses to correct uncomplicated refractive error did not experience an improvement in signs or symptoms of ocular surface disease.